Stakeholder Satisfaction Level in the Delivery of Services of a Fish Port Complex in the Philippines - Jesus Briones; Rogelio P Danganan; Lloyd M Macalalad; Marlon T Crodua; Arman Glen M Bautista; Joanna Paula E Verano (Logistic and Operation Management Research (LOMR), 2025)
Fish port complexes play a crucial role in the post-harvest fisheries sector, serving as central hubs for landing, processing, and distributing fish products. This study assessed stakeholder satisfaction with service delivery at a fish port complex in the Philippines, focusing on 325 stakeholders (fish brokers, buyers, and ice dealers/ crushers). Employing a mixed-methods approach, combining both quantitative and qualitative research designs, data were collected through an adapted questionnaire administered face-to-face with respondents, along with semi-structured interviews to capture in-depth qualitative insights. The quantitative data were analyzed using frequency, percentage, weighted mean, and Pearson correlation coefficient. Thematic analysis was employed to analyze the qualitative responses, identifying key themes and recurring patterns within the data. The findings revealed that stakeholders were satisfied with the services delivered at the fish port complex in terms of billing, payment, accreditation and renewal of permits, as well as the issuance of permits to conduct business. Furthermore, perceptions of respondents in the four service areas showed no significant differences across demographic profile, indicating that improvements in these areas would likely benefit all stakeholders. However, challenges including billing and payment issues, bureaucratic delays, slow processing, and complex permit processes have negatively impacted satisfaction of the fish brokers. Based on these findings, the study proposed strategies to enhance the service quality of the fish port complex. These improvements are also deem essential for other fish port complexes aiming to enhance its operational efficiency, build stakeholder trust, and ensure the sustainable development of the fisheries sector.